2017
DOI: 10.1080/0284186x.2017.1287949
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric advantages of a clinical daily adaptive plan selection strategy compared with a non-adaptive strategy in cervical cancer radiation therapy

Abstract: Background: Radiation therapy (RT) using a daily plan selection adaptive strategy can be applied to account for interfraction organ motion while limiting organ at risk dose. The aim of this study was to quantify the dosimetric consequences of daily plan selection compared with non-adaptive RT in cervical cancer. Material and methods: Ten consecutive patients who received pelvic irradiation, planning CTs (full and empty bladder), weekly post-fraction CTs and pre-fraction CBCTs were included. Non-adaptive plans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
0
37
1
Order By: Relevance
“…Current IGART strategies are mainly guided by the influence of the bladder filling on target coverage, and motion patterns are identified at time of treatment planning [5,6,8,29]. We found that target coverage was dependent on a combination of various factors, e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Current IGART strategies are mainly guided by the influence of the bladder filling on target coverage, and motion patterns are identified at time of treatment planning [5,6,8,29]. We found that target coverage was dependent on a combination of various factors, e.g.…”
Section: Discussionmentioning
confidence: 94%
“…At each treatment fraction, CBCT images enable the optimal treatment plan to be chosen among those of the library ("planof-the-day"). This strategy appears to be adequate to compensate for uterine motions [9][10][11]. However, such a library does not handle per-treatment deformations that are not represented in the planning CTs.…”
Section: Xternalmentioning
confidence: 99%
“…The motion includes displacement and shape changes of the uterus and variation in filling of the bladder and rectum [10,11]. Inter-and intra-fraction motion may compromise target coverage and OAR sparing in photon treatment [12], but can be even more concerning in proton therapy due to the additional range uncertainty [13]. Due to the range uncertainty and the lack of high quality in-room imaging, proton therapy up until now has rarely been used to treat gynaecological malignancies.…”
mentioning
confidence: 99%